THE IMPACT OF INDIAN OCEAN HIGH PRESSURE SYSTEM ON RAINFALL AND STREAM FLOW - Rehman, S. U.; Nasir, H.; Zia, S. S.; Ansari, W. A.; Saleem, K.; Tayyab, N. (The Nucleus, 2012)
Centre of Action approach is very useful in getting insight of rainfall and stream flow variability of specific region. Hameed et al. [17] showed that Inter-annual variability of Gulf Stream north wall is influenced by low Icelandic pressure system and has more statistically significant correlation than North Atlantic Oscillation (NAO) with longitude of Icelandic low. This study also aims to explore possible relationships between rainfall and stream flow in Collie river catchment in Southwest Western Australia (SWWA) with Indian Ocean high pressure dynamics. The relationship between rainfall and stream flow with Indian Ocean high pressure system have been investigated using correlation analysis for early winter season (MJJA), lag correlation for MJJA versus SOND rainfall and stream flow are also calculated and found significant at 95% confidence level. By investigating the relationship between COA indices with rainfall and stream flow over the period 1976-2008, significant correlations suggests that rainfall and stream flow in Collie river basin is strongly influenced by COA indices. Multiple correlations between rainfall and stream flow with Indian Ocean high pressure (IOHPS and IOHLN) is 0.7 and 0.6 respectively. Centers of Action (COA) indices explain 51% and 36% of rainfall and stream flow respectively. The correlation between rainfall and stream flow with IOHPS is -0.4 and -0.3 whereas, with IOHLN is -0.47 and -0.52 respectively.